Pengaruh Bahan Ajar Berbasis Contextual Teaching and Learning (CTL)Terhadap Kemampuan Penalaran Matematis Siswa SMA - Anggria Septiani Mulbasari; Nora Surmilasari (Jurnal Elemen, 2018)
This study aims to determine the influence of teaching materials, especially on the uncertainty material based on Contextual Teaching and Learning (CTL) on the mathematical reasoning ability of high school students. This research is a Quasi-experimental research design using Posttest-Only Control Group Design. This research was conducted at SMA Negeri 8 Palembang. Where class XI.IPA 6 as an experimental class is taught with teaching materials based on CTL and class XI.IPA 5 as a control class taught by conventional methods. At the end of the meeting the two classes were given tests to measure the ability of mathematical reasoning, then the results were compared with the t test with the condition of normality and homogeneity tested first. The result of t test shows that the significance value 0,00 0,05 based on hypothesis testing criterion H0 rejected means Ha accepted and it can be concluded that "There is significant influence of teaching materials in the form of Student Activity Sheet (LKS) based on Contextual Teaching and Learning (CTL) uncertainty material to the mathematical reasoning ability of high school students.